Membangun Karakter Anti Korupsi dan Anti Gratifikasi di Era Digital via Media Sosial sebagai Alat Edukasi di Sekolah - Suprihno, Suprihno; Rohmawati, Eti (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This research aims to develop an anti-corruption character among students through the use of social media as an educational tool in schools. In the digital era, social media has become an effective platform for conveying moral and ethical values. Using qualitative methods with a literature study approach and constructive analysis, this research examines various sources related to the use of social media in education and its role in shaping student character. The findings show that social media can be used as a communication tool and a means to disseminate information about corruption. Integrating anti-corruption content into social media activities in schools can create a learning environment that supports and encourages ethical behaviour. This research makes a significant contribution to the development of relevant character education programs in the digital era and increases students' awareness of the importance of integrity and social responsibility. By understanding the dynamics of social media and digital technology, educators and policymakers can utilize these tools to combat corruption and promote ethical values in society. These results show the great potential of social media in supporting character education and creating a generation with integrity.